To aid or not to aid: Foreign aid and productivity in cross-country regressions - Pablo Selaya (Institute for Advanced Development Studies (INESAD), 2005)
The paper reexamines empirically the robustness of competing theories of foreign aid effectiveness. By shifting the focus from the effects of aid on income to effects of aid on productivity, it is possible to put to test 3 existing theories of foreign aid effectiveness. The results provide support for the hypotheses that (i) aid has a positive effect in fostering growth of average productivity, (ii) aid doesn't operate with diminishing returns, and (iii) the magnitude of the total effect depends on climate-related circumstances. The results support the policy recommendation previously made in the literature to seriously reconsider the conditionality rule for foreign aid disbursements.
Keywords: F35; 330; Foreign Aid; cross-country; conditionality